2000
DOI: 10.1182/blood.v96.2.443.014k32_443_451
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant EBV+ T-cell lymphoproliferative disorder following acute/chronic EBV infection: a distinct clinicopathologic syndrome

Abstract: This study describes the clinicopathologic features of 5 patients who developed a fulminant Epstein-Barr virus (EBV)-positive clonal T-cell lymphoproliferative disorder (LPD) after acute EBV infection. One additional patient developed a similar disorder in the setting of long-standing chronic active EBV infection. Detailed immunophenotyping, in situ hybridization for EBV early RNA-1 (EBER1) and polymerase chain reaction (PCR) analyses for immunoglobulin (Ig) heavy chain and T-cell receptor (TCR)-gamma gene rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 48 publications
2
117
1
1
Order By: Relevance
“…Epstein-Barr virus infection is associated with several human malignancies including Burkitt's lymphoma, Hodgkin's disease, post-transplantation lymphoproliferative disorders, fulminant EBV-positive T-cell lymphoproliferative disorder following chronic active EBV infection (CAEBV), nasopharyngeal carcinoma, gastric carcinoma, smooth muscle tumor in immunosuppressed patients, thymic carcinoma, and various types of peripheral T-cell and NK/T-cell proliferative disease/ lymphoma. 1,2,[11][12][13][14][15][16][17][18][19][20][21][43][44][45][46][47][48][49][50][51] In this study we found EBV genome and expression of EBER in the hepatic T-cell infiltrates of 61.4% and 38.6% of the patients, respectively. Expression of EBER was more commonly found in patients from groups C and D. The EBV serological study showed significantly high titers of anti-VCA-IgG and anti-EA-IgG in patients compared to our previous controls, 1 although the titer of the two groups overlapped to a considerable extent.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Epstein-Barr virus infection is associated with several human malignancies including Burkitt's lymphoma, Hodgkin's disease, post-transplantation lymphoproliferative disorders, fulminant EBV-positive T-cell lymphoproliferative disorder following chronic active EBV infection (CAEBV), nasopharyngeal carcinoma, gastric carcinoma, smooth muscle tumor in immunosuppressed patients, thymic carcinoma, and various types of peripheral T-cell and NK/T-cell proliferative disease/ lymphoma. 1,2,[11][12][13][14][15][16][17][18][19][20][21][43][44][45][46][47][48][49][50][51] In this study we found EBV genome and expression of EBER in the hepatic T-cell infiltrates of 61.4% and 38.6% of the patients, respectively. Expression of EBER was more commonly found in patients from groups C and D. The EBV serological study showed significantly high titers of anti-VCA-IgG and anti-EA-IgG in patients compared to our previous controls, 1 although the titer of the two groups overlapped to a considerable extent.…”
Section: Discussionmentioning
confidence: 83%
“…Mature NK/T-cell neoplasms are highly associated with Epstein-Barr virus (EBV) infection, and it is likely that EBV plays an important role in tumorigenesis. 1,2,[6][7][8] The EBV-associated lymphoproliferative disorders of the T cell include EBV-associated hepatitis, 10 fulminant (fatal) EBVpositive T-cell lymphoproliferative disorder following acute and chronic EBV infection, [11][12][13][14] hepatic peripheral T-cell lymphoma, 2,15 extranodal NK/T-cell lymphoma, nasal-type, [16][17][18] enteropathy-type intestinal T-cell lymphoma, 19 nonhepatosplenic g / d T-cell lymphomas of various sites, 20 and angioimmunoblastic T-cell lymphoma and peripheral T-cell lymphoma, unspecified. 21 Peripheral T-cell proliferative diseases/lymphomas can manifest with nodal and extranodal involvement.…”
mentioning
confidence: 99%
“…These clinical findings, in conjunction with markedly elevated antibody titres to EBV-associated antigens, were consistent with chronic active EBV (CAEBV) infection. [14][15][16][17][18] Patients with sinonasal disease presented with symptoms of chronic rhinosinusitis and nasal obstruction and congestion, with or without deviated nasal septum. In one patient, the tumour was diagnosed from a biopsy of tissue taken during surgery for septal repair.…”
Section: L I N I C a L F E A T U R E Smentioning
confidence: 99%
“…Recently, diagnostic criteria have been proposed (7,17). Although the pathogenesis and etiology were unclear, it has been reported that the clonal expansion of EBV-infected T or NK cells might be associated with the development of CAEBV (5,6,8,9,18). However, oligoclonal expansion of EBV-infected lymphocyte has been reported, so it is not clear whether CAEBV is truly a monoclonal disorder or not (10).…”
Section: Discussionmentioning
confidence: 99%